Integrated approach for the analysis of neonicotinoids in fruits and food matrices. (15th March 2022) - Calza, Paola; Guarino, Barbara; Dal Bello, Federica; Dioni, Anna; Bergero, Marco; Medana, Claudio
Highlights: Separation and detection of five neonicotenoids (acetamiprid, clothianidin, imidacloprid, thiacloprid and thiamethoxam) in 67 vegetables samples via HPLC-MS by employing QueChERs for extraction and purification. Identification and characterization of acetamiprid transformation products via HPLC-HRMS after induced photocatalysis with TiO2 and development of a method to search for them in real food samples. Evaluation of acute toxicity of acetamiprid and its transformation products using marine bacterium Vibrio fischeri. Recognition of transformation products in hazel leaves. Abstract: We searched for five neonicotenoids (namely acetamiprid, clothianidin, imidacloprid, thiacloprid and thiamethoxam) in 67 samples of fruits, leaves, pollen and honey via HPLC-MS by employing QueChERs for extraction and purification. Clothianidin was never detected, while imidacloprid was identified in apple (9.2 µg/kg) and pollen (18–28 µg/Kg), thiacloprid in peaches (21–35 µg/kg) and acetamiprid was identified in the hazel leaves (1266 µg/kg), honey (13–26 µg /Kg) and pollen (11–24 µg/kg). Since the levels found of acetamiprid in hazel, honey and pollen were concerning, we accomplished a study to identify and characterize the possible transformation products via a laboratory simulation. The methodology exploited the analysis by HPLC-HRMS and its application in all matrices. We identify twelve transformation products, whose formation involved dimerization, hydroxylation, oxidation, demethylation and cleavage of the molecule. Three of them were also detected in hazel leaves.